Structural transformations and the lack of inclusive growth: The case of Chile - Andrés Solimano; Gabriela Zapata-Román (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2019)
This paper describes the structural transformations that Chile has experienced in the last 50 years and how they have contributed-or not-to inclusive growth and genuine economic modernization from a historical perspective. The empirical analysis of the paper shows a premature deindustrialization process since the 1970s, continuing to the present. We observe in the transition from the import-substitution industrialization strategy to the outward-oriented neoliberal model of high inequality, a decline in the value-added shares of manufacturing and agriculture and a rise in services (mainly financial services, insurance, and real estate) with ups and downs in mining shares. These trends are more emphasized in employment shares, with the decline in relative employment generation in agriculture and manufacturing going directly to the services sector that now accounts for two-thirds of total employment in the economy. The trend of persistent deindustrialization and high inequality is worrisome and could negatively affect Chile's ability to achieve structural transformations towards higher and more sophisticated levels of productive development and technological advancement.
Keywords: L16; L52; N1; O14; O25; 330; Chile; deindustrialization; inclusive growth; inequality; structural transformations